Konsekuensi Pemidanaan Bagi Warga Binaan Yang Mengalami Gangguan Jiwa(Studi Kasus di Lapas Kelas IIA Sragen) - Nuryanto, Wahyu Sigit; , Dr. Natangsa Surbakti, S.H., M.Hum; , Bambang Sukoco S.H.,M.H (2016)
Guiding and Founding Inmates who have mental disorders at the Correctimal Institution Class IIA Sragen done by legislation. In reality, Inmates who have mental disorders are as human beings and human resources should be treated well and humanely so that the right of Inmates are not violated. Because Inmates who have mental disordersare having right of obtaining health care. The obstractim of guiding for Inmates who have mental disorders is the lack of professimal staff, so the Correctional Institutionin Colaboration with the Hospital of Sragen in the treatment of psychiatric Inmates so that the right of Inmates who have mental disorders have been completely.